Influence of Tele-Evangelism Programmes on Moral Adjustments of Residents of Lagos and Oyo States, Nigeria (2012)
Television, a typical mass medium strives to update viewers on happenings around them with the hope of influencing change in actions, attitudes, opinions or belief. This is done through different types of programmes and messages being disseminated, including specialised Christian broadcastings. The Christian broadcasting industry has become a big industry, notwithstanding the degenerating moral state of the society. Corruption, greed, selfishness, dishonesty and immorality have become the driving force which shapes the social values. However, there is dearth of studies to empirically validate the importance and role of tele-evangelism in Nigeria. This study, therefore, investigated the influence of tele-evangelism programmes on moral adjustment of residents of Lagos and Oyo States, Nigeria. Descriptive survey research design of the ex post facto type was adopted. Two thousand two hundred and forty respondents, viewers of five different tele-evangelism programmes on BCOS, Galaxy, NTA Ibadan, AIT, LTV & NTA (10), public and private stations in Oyo and Lagos States (states with high tele-evangelistic exposure and social maladies) were selected through a combination of purposive, stratified and simple random sampling techniques. Tele-evangelism Scale (r=0.78) and Moral Adjustment Rating Scale with 5 independent self-developed sub-rating scales Financial Crime (r=0.72), Sexual Immorality (r=0.80), Violent Crime (r=0.77), Materialism (r=0.80) and Sacredness of Life (r=0.81) were used for data collection. These were complimented with six sessions of Focus Group Discussion (FGDs), conducted with selected viewers of the chosen tele-evangelism programmes; Christians and Muslims, of both sexes, varying ages and levels of education across centres. Three research questions were answered and two hypotheses tested at 0.05 level of significance. Data were analysed using descriptive statistics; Pearson Product Moment Correlation and Multiple regression. Tele-evangelism viewing of 89.3% was recorded and disaggregated on both programme and TV station basis as follows, programme: LW (35.1%), RH (31.3%), S&M (19.2%), HDL (13.8%) and MT (1.3%); TV station: BCOS (21.0%), NTA Ibadan (9.0%), Galaxy Ibadan (5.0%), LTV (18.0%), AIT (24.0%) and NTA 10 (8.0%). Tele-evangelism significantly influenced moral adjustments of viewers of the programmes (Fl3, 2237) = 15.61, p < 0.05). The relative influence of the five different favourite tele-evangelism programmes on moral adjustments of viewers was as follows: LW (β = 0.79; p<0.05), RH (β = 0.70; p<0.05), S&M (β=0.43; p<0.05), HDL (β=0.31; p<0.05), and MT (β=0.03; p<0.05). Furthermore, tele-evangelism significantly influenced the components of moral adjustments as follows: sexual immorality (β=-0.13; p<0.05), violent crime (β=-0.19; p<0.05), financial crime (β=-0.17; p=<0.05), sacredness of life (β=0.14; p=0.05) and materialism (β=0.11; p<0.05). Influence of tele-evangelism on moral adjustments correlated with viewers’ characteristics in the following order: level of exposure (r= 0.37; p<0.05), level of education (r=0.35; p<0.05) and age (r= -0.34; p<0.05). The FGD results showed that tele-evangelism enhanced moral adjustments of viewers at low level; some tele-evangelists are self seeking; only flaunting their wealth on TV screen. Though tele-evangelism influenced moral adjustments among viewers, the National Broadcasting Commission, the Christian coordinating bodies and television stations should collaborate on tele-evangelism programming, to reduce to the barest minimum materialistic tendency among the citizenry.